Artificial insemination in pig, its status and future perspective in India: A review - SINGH, MAHAK; MOLLIER, R TALIMOA (The Indian Journal of Animal Sciences, 2021)
The pig production must be sustainable, efficient and competitive to minimize its impact on environment. There is argument to keep fewer breedable animals to produce more numbers of piglets. In India, pig rearing is still done on traditional manner with low productivity. Artificial insemination (AI) is the best reproductive technology available in the current scenario for enhancing the efficiency of pig production in a sustainable way. This in pig involves, collection of semen, processing in laboratory, packaging in 80 to 90 ml semen pouch containing two to three billion spermatozoa and inseminating the sow at correct time. AI in pig is used widely in the world with the use of freshly diluted semen. The use of AI has allowed significant improvement in swine population over the world. Besides genetic improvement, it allows for better maintenance of farm record, saving farm labour and prevents disease transmission. Artificial insemination in northeast India has been introduced only recently but the response from the different stakeholders is quite favourable. In order to replicate the successes achieved in different countries, a proper understanding of the technique, its adaptability to local conditions and the regulations need to be put in place. The establishment of support services is vital to achieve success. The technology has the potential for enhancing the profitability of pig farming in sustainable way. To reap the full potential of this technology, concerted efforts are needed from all stakeholders.